Poly(2-ethyl-2-oxazoline) conjugates with doxorubicin for cancer therapy: In vitro and in vivo evaluation and direct comparison to poly[N-(2-hydroxypropyl)methacrylamide] analogues. (November 2017) - Sedlacek, Ondrej; Monnery, Bryn D.; Mattova, Jana; Kucka, Jan; Panek, Jiri; Janouskova, Olga; Hocherl, Anita; Verbraeken, Bart; Vergaelen, Maarten; Zadinova, Marie; Hoogenboom, Richard; Hruby, Martin
Abstract: We designed and synthesized a new delivery system for the anticancer drug doxorubicin based on a biocompatible hydrophilic poly(2-ethyl-2-oxazoline) (PEtOx) carrier with linear architecture and narrow molar mass distribution. The drug is connected to the polymer backbone via an acid-sensitive hydrazone linker, which allows its triggered release in the tumor. The in vitro studies demonstrate successful cellular uptake of conjugates followed by release of the cytostatic cargo. In vivo experiments in EL4 lymphoma bearing mice revealed prolonged blood circulation, increased tumor accumulation and enhanced antitumor efficacy of the PEtOx conjugate having higher molecular weight (40 kDa) compared to the lower molecular weight (20 kDa) polymer. Finally, the in vitro and in vivo anti-cancer properties of the prepared PEtOx conjugates were critically compared with those of the analogous system based on the well-established PHPMA carrier. Despite the relatively slower intracellular uptake of PEtOx conjugates, resulting also in their lower cytotoxicity, there are no substantial differences in in vivo biodistribution and anti-cancer efficacy of both classes of polymer-Dox conjugates. Considering the synthetic advantages of poly(2-alkyl-2-oxazoline)s, the presented study demonstrates their potential as a versatile alternative to well-known PEO- or PHPMA-based materials for construction of drug delivery systems. Graphical abstract: